Penyusunan Laporan Keuangan UMKM Berdasarkan Sak EMKM: Studi Kasus pada Mebel Kerajinan Jepara - Mathilda Novania Da Lopez; Wilhelmina Mitan; Paulus Libu Lamawitak (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to identify and analyze the preparation of financial statements based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in the Mebel Kerajinan Jepara business. A descriptive qualitative approach was employed using primary data obtained directly from business owners. Data collection techniques included in-depth interviews, observation of accounting records, and documentation of transaction evidence and records used in preparing financial statements. The data were analyzed descriptively to present systematic, factual, and accurate information about the actual accounting practices in the field. The findings reveal that the preparation of financial statements at Mebel Kerajinan Jepara has not yet fully complied with SAK EMKM. The business only keeps simple records of income and expenses in a notebook without producing complete financial statements such as the statement of financial position, income statement, and notes to the financial statements. The main constraints identified are the limited understanding of the business owners regarding the importance of accounting and the absence of human resources with accounting expertise. These findings highlight the need for assistance, training, and capacity building for business owners in the field of accounting to produce standardized financial reports, enhance business credibility, and support decision-making as well as access to financing. Thus, this study is expected to serve as a reference for local governments, educational institutions, and other related parties in providing accounting guidance to micro and small business actors.